The ultimate horse behavior and training book : enlightened and revolutionary solutions for the 21st century - Tellington-Jones, Linda; Lieberman, Bobbie (North Pomfret, Vt. : Trafalgar Square Pub., 2006)
A superbly illustrated instructional manual offering groundbreaking, step-by-step solutions for hundreds of horse behavior, health, and training problems.
Part one: An overview of the Tellington Method; Part two: Behavior and training issues A-Z; Part three: The Tellington Method how-to-guide.
Includes bibliographical references (pages 311-313) and index.
107218
Keywords: Horses -- Behavior; Horses -- Training